Targeting endothelial tight junctions to predict and protect thoracic aortic aneurysm and dissection. (14th January 2023) - Yang, Xueyuan; Xu, Chen; Yao, Fang; Ding, Qianhui; Liu, Hao; Luo, Congcong; Wang, Daidai; Huang, Jiaqi; Li, Zhiqing; Shen, Yicong; Yang, Weijie; Li, Zhuofan; et al.
Abstract: Aims: Whether changes in endothelial tight junctions (TJs) lead to the formation of thoracic aortic aneurysm and dissection (TAAD) and serve as an early indicator and therapeutic target remains elusive. Methods and results: Single-cell RNA sequencing analysis showed aberrant endothelial TJ expressions in the thoracic aortas of patients with TAAD. In a β-aminopropionitrile (BAPN)-induced TAAD mouse model, endothelial TJ function was disrupted in the thoracic aortas at an early stage (5 and 10 days) as observed by a vascular permeability assay, while the intercellular distribution of crucial TJ components was significantly decreased by e n face staining. For the non-invasive detection of endothelial TJ function, two dextrans of molecular weights 4 and 70 kDa were conjugated with the magnetic resonance imaging (MRI) contrast agent Gd-DOTA to synthesize FITC-dextran-DOTA-Gd and rhodamine B-dextran-DOTA-Gd. MRI images showed that both probes accumulated in the thoracic aortas of the BAPN-fed mice. Particularly, the mice with increased accumulated signals from 5 to 10 days developed TAAD at 14 days, whereas the mice with similar signals between the two time points did not. Furthermore, the protease-activated receptor 2 inhibitor AT-1001, which seals TJs, alleviated the BAPN-induced impairment of endothelial TJ function and expression and subsequently reduced TAAD incidence. Notably, endothelial-targeted ZO-1 conditional knockout increased TAAD incidence. Mechanistically, vascular inflammation and edema were observed in the thoracic aortas of the BAPN-fed mice, whereas these phenomena were attenuated by AT-1001. Conclusion: The disruption of endothelial TJ function is an early event prior to TAAD formation, herein serving as a potential indicator and a promising target for TAAD. Structured Graphical Abstract: Structured Graphical Abstract The disruption of endothelial tight junctions (TJs) emerged as an early pathological change in the progression of thoracic aortic aneurysm and dissection (TAAD). Evaluating the function of the endothelial TJs by magnetic resonance imaging (MRI) could predict the occurrence of TAAD, and sealing TJs prevented the incidence of TAAD. Inflammatory cells and water transported across the impaired endothelial TJs caused vascular inflammation and edema and eventually caused TAAD.